Faktorer som påverkar spridningen av West Nile Virus och risken att viruset sprids till Sverige och Nordeuropa - Segall, Michael (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2010)
West Nile Fever and West Nile Encephalitis are caused by the flavivirus West Nile Virus (WNV). West Nile Virus is now a dangerous threat for horses, birds and humans.